Optimization of Bus Body Frame Structure for Weight Minimizing with Constraint of Natural Frequency using Adaptive Single-Objective Method - Haryanto, Ismoyo; Raharjo, Fuad; Kurdi, Ojo; Haryadi, Gunawan; Santosa, Sigit; Gunawan, Leonardo (http://dx.doi.org/10.31427/IJSTT.2018.1.1.2, 2018)
The objective of this work is to analyze and optimize a bus frame structure using Finite Element Method in dynamic conditions. The bus body geometry was obtained directly from the three-dimensional Computer-Aided Design files. The optimization was conducted to determine the minimum weight of the bus frame structure without violating the specified natural frequency constraints. The design variable is the thickness of the bus body frame. In present study, Adaptive Single Objective method was chosen as an optimizer method. The results show that the structural weight of the bus frame can be reduced about 8% without changing its dynamic characteristic.